Pengaruh Kadar Garam Dapur Terhadap Suhu Makanan yang Dimasak dengan Microwave - Wasir Nuri,MT (Eksergi, 2010)
Many people cook by using microwave oven.  There are some reasons for health and the others for practice. Generally they do not know that food temperature is depends on amount of polar compound. Salt is polar compound hence salt content  influenced temperature of food. The objective of research was to determine salt  content to food temperature which is cooked by microwave. This research was simulated by mixing 20 g starch and 20 g salt water with salt variation from 0 to 3,2%. The mixed was put  into Becker glass 100 cc. and heated in microwave oven in low power  level until medium.  The temperature was measured every 2,5 minute until 15 minute. This research  show that salt and electricity power influence the temperature. For examples electricity power level-low, in 15 minute the temperature increase from 37oC to 73 oC at 3,2 % salt content, while at salt 0% and electricity power medium level the temperature increase  up to 90 o C.